Pendampingan Nagari Wisata Berbasis Sustainable Tourism Development di Nagari Sikabu-kabu Tanjung Haro Padang Panjang - Nur Ari Sufiawan; Verinita Verinita; Ranny Fitriana Faisal; Weriantoni Weriantoni; Bintang Rizky Abdullah Majo Saibah; Yindrizal Yindrizal; Susiana Susiana; Faisal Ali Ahmad; Devi Yulia Rahmi; Musbatiq Srivani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2021)
Nagari Sikabu-kabu Tanjung Haro Padang Panjang is the the main gate in the regency of Lima Puluh Kota and should be foremost Nagari. The tourism sector has beautiful natural conditions and a great view of Talang and Kayu Kolek panorama. The purpose of the service was to develop Nagari Sikabu-kabu Tanjung Haro Padang Panjang as a tourist village. It would attract tourists to travel, which is carried out with a tourism village development strategy. Through Sustainable Tourism Development (STD) steps by conducting Focus Group Discussion (FGD) activities with the community, including tourism managers, Micro Small and Medium Enterprises (MSME) actors, and the leaders of Nagari. The methods used were lectures, discussions, business consultations, and assistance in creating and managing Nagari tourism websites. This activity might provide insights into managing a touristic village by increasing the knowledge and skills of the Nagari tourism managers and community surroundings.